2022
DOI: 10.1039/d1ma01112j
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in chemical recycling of polyethylene terephthalate waste into value added products for sustainable coating solutions – hopevs. hype

Abstract: In the current era of globalization, plastics are an indispensable part of our daily life; from morning toothbrush to night dinner table, plastics are everywhere in our daily life. In...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
57
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(82 citation statements)
references
References 120 publications
(126 reference statements)
0
57
0
Order By: Relevance
“…Polyesters, especially poly­(ethylene terephthalate) (PET), are widely used in packaging (e.g., beverage bottles, thermally stabilized films), textiles (fibers), and many engineering applications because of their excellent mechanical strength, chemical resistance, excellent electrical insulation, and thermal resistance. Recycled PET (rPET) is mainly obtained from beverage bottles because a better collection infrastructure exists for bottles than for other types of municipal solid waste (MSW). Approximately 40% of rPET in Europe is downcycled for low-end applications (e.g., nonfood grades) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyesters, especially poly­(ethylene terephthalate) (PET), are widely used in packaging (e.g., beverage bottles, thermally stabilized films), textiles (fibers), and many engineering applications because of their excellent mechanical strength, chemical resistance, excellent electrical insulation, and thermal resistance. Recycled PET (rPET) is mainly obtained from beverage bottles because a better collection infrastructure exists for bottles than for other types of municipal solid waste (MSW). Approximately 40% of rPET in Europe is downcycled for low-end applications (e.g., nonfood grades) .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, PET that is currently not recycled is valuable enough to warrant research and development (R&D) efforts to increase collection and recovery through advanced recycling techniques or by maximizing features that facilitate recycling, such as enhanced labeling and the reduction of secondary materials. Efforts have been focused on recycling PET, the most recycled plastic. , However, the rPET is usually of low quality (e.g., poor mechanical properties, low viscosity) because of the molecular weight reduction that occurs during the melt-processing of this polymer caused by hydrolytic reactions . Chemical and mechanical recycling are currently used as end-of-life solutions for rPET.…”
Section: Introductionmentioning
confidence: 99%
“…The global consumption of PET was valued at $43.81 billion in 2019 with a compound annual growth rate of 11%, which predicts $68.33 billion global consumption by 2023 2 . Researchers reported that the global demand of PET will reach 22.65 million tons by 2025 with a current value of $44.1 billion 3 …”
Section: Introductionmentioning
confidence: 99%
“…The widespread daily consumption of PET-made (polyethylene terephthalate) products in modern life has led to an acute problem of PET waste disposal [ 18 ] because PET is known to be non-biodegradable in nature. That is why the recycling of PET [ 19 ] has become one of the most important scientific topics regarding that only 28.4% of PET is recycled [ 20 ]. The search for new value-added and useful products from PET waste led to some attempts to make the epoxy resins [ 21 , 22 ], and new hardeners [ 23 ].…”
Section: Introductionmentioning
confidence: 99%